Performance comparison of biomethane, natural gas and gasoline in powering a pickup truck. Issue 8 (9th August 2022) - Aggarangsi, Pruk; Moran, James; Koonaphapdeelert, Sirichai; Tippayawong, Nakorn
Abstract: This paper compares the operating performance of biomethane with both natural gas and gasoline in a small pickup truck. Three different purity levels were used for the biomethane, with the lowest having an 83% methane concentration. The purpose of this paper is to compare the performance of a biomethane powered vehicle, by measuring its power, torque, emissions, fuel efficiency and cost to examine the benefits and issues with using biomethane. The results show a higher power level for gasoline but similar performance level for all three biomethane purities and pure natural gas. The emissions for biomethane were lower than gasoline and the resulting fuel cost was over twice as economical per kilometer travelled.